Jesuits and the Natural Sciences in Modern Times, 1814-2014 Brill's Research Perspectives in Jesuit Studies - Udías, Agustín (Brill Research Perspectives in Humanities and Social Sciences, 2019)
From 1814, linked to their educational work, Jesuits made significant contributions to the natural sciences, especially in the fields of astronomy, meteorology, seismology, terrestrial magnetism, mathematics, and biology in a worldwide network of universities, secondary schools and observatories.; Readership: All interested in the history of Jesuits and their contribution to the natural sciences, in science and religion and in general in the history of science.